A bibliometric analysis of eclectic approaches in reading instruction for students with learning difficulties - Nursara Abdul Munir; Syar Meezee Mohd Rashid (Journal of Learning and Educational Policy, 2025)
Reading instruction for students with learning difficulties has increasingly emphasised the need for flexible and integrative pedagogical approaches. In response to the growing and fragmented body of research on eclectic approaches to reading instruction, this study aims to provide a comprehensive bibliometric overview of scholarly publications in this field. Using a bibliometric research design, data were retrieved from the Scopus database and analysed using descriptive statistics and network-based techniques. A total of 522 journal articles published between 2000 and 2025 were examined to identify publication trends, country-level research contributions, international collaboration patterns, and thematic structures based on keyword co-occurrence analysis. The findings reveal a steady growth in publication output over time, indicating increasing scholarly interest in eclectic and integrated instructional approaches within special education and literacy research. Research output remains concentrated in a small number of countries, particularly English-speaking contexts, while international collaboration is characterised by relatively fragmented co-authorship networks. The keyword co-occurrence analysis further indicates that research in this area is thematically diverse and interdisciplinary, with emerging links to technology-enhanced and STEM-related instructional contexts. Overall, this study provides a structured and data-driven mapping of the intellectual landscape of research on eclectic approaches to reading instruction for students with learning difficulties, offering valuable insights for future research, policy, and instructional practice.